The indifference towards democracy in Latin America - Monsivais-Carrillo, Alejandro (Facultad Latinoamericana de Ciencias Sociales, Sede Ecuador, 2020)
Despite the increasing political discontent, manifested in the emergent democracies and consolidated as well, citizens’ support for democracy seemed stable in most countries. Recently, however, some studies have uncovered signs of an increasing disconnection with democracy’s values and institutions. This study argues that a specific expression of citizens’ estrangement from democracy is political indifference: the opinion that living in a democratic or an authoritarian regime makes no difference. This statement is supported by the analysis of four surveys conducted in 18 Latin American countries from 2013 to 2017. The evidence indicates that even though there is a preference for democracy in the region, this preference is not very high. A considerable segment of the population declares being indifferent, rather than choosing the authoritarian option. The analysis shows that the attitude of political indifference is associated with a heightened discontent about the performance of the political system. It is also more likely that people who declare they are politically indifferent distrust others more and are more likely to be women, teenagers, less educated, or live in a low-income household. The evidence suggests that for a significant number of citizens democracy is an abstract notion that does not create political attachment.